COSMOGENIC 14CO FOR ASSESSING THE OH-BASED SELF-CLEANING CAPACITY OF THE TROPOSPHERE. Issue 4 (1st August 2022) - Brenninkmeijer, Carl A M; Gromov, Sergey S; Jöckel, Patrick
ABSTRACT: An application of radiocarbon ( 14 C) in atmospheric chemistry is reviewed. 14 C produced by cosmic neutrons immediately forms 14 CO, which reacts with hydroxyl radicals (OH) to 14 CO2 . By this the distribution and seasonality (the lifetime of 14 CO is ∼1 month) of the pivotal atmospheric oxidant OH can be established. 14 CO measurement is a complex but unique application which benefitted enormously from the realization of AMS, bearing in mind that 14 CO abundance is of the order of merely 10 molecules per cm 3 not only provides 14 CO an independent measure for the OH based self-cleansing capacity of the troposphere, but also enabled detection of 14 C production due to high energy solar protons in 1989. Although its production takes place throughout the atmosphere and does not have the character of a point source, transport processes in the atmosphere affect the distribution of 14 CO. Vertical mixing in the troposphere renders gradients in its production rate less critical, but considerable meridional gradients exist. One question has remained open, namely confirmation of calculated 14 C production by direct measurement. A new sampling method is proposed. The conclusions are a guide to future work on 14 CO in relation to OH and atmospheric transport.